Preemptive Interferon-α Therapy Could Protect Against Relapse and Improve Survival of Acute Myeloid Leukemia Patients After Allogeneic Hematopoietic Stem Cell Transplantation: Long-Term Results of Two Registry Studies - Shen, Meng-Zhu; Zhang, Xiao-Hui; Xu, Lan-Ping; Wang, Yu; Yan, Chen-Hua; Chen, Huan; Chen, Yu-Hong; Han, Wei; Wang, Feng-Rong; Wang, Jing-Zhi; Zhao, Xiao-Su; Qin, Ya-Zhen; et al. (Frontiers in Immunology, 2022)
For allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients, preemptive interferon-α (IFN-α) therapy is considered as a useful method to eliminate the minimal residual disease (MRD). Our purpose is to assess the long-term efficacy of preemptive IFN-α therapy in acute myeloid leukemia (AML) patients following allo-HSCT based on two registry studies (#NCT02185261 and #NCT02027064). We would present the final data and unpublished results of long-term clinical outcomes with extended follow-up. We adopted polymerase chain reaction (PCR) and multiparameter flow cytometry (MFC) to monitor MRD, and a positive result of bone marrow specimen examined by either of them would be identified as the MRD-positive status. Subcutaneous injections of recombinant human IFN-α-2b were performed for 6 cycles, and prolonged IFN-α therapy could be permitted at the request of patients. The median cycles were 3.5 (range, 0.5–30.5) cycles. A total of 9 patients suffered from grade ≥3 toxicities (i.e., infectious: n=6; hematologic: n=3). The 6-year cumulative incidences of relapse and non-relapse mortality following IFN-α therapy were 13.0% (95% confidence interval [CI], 5.4–20.6%) and 3.9% (95% CI, 0.0–17.6%), respectively. The probability of disease-free survival at 6 years following IFN-α therapy was 83.1% (95% CI, 75.2–91.9%). The probability of overall survival at 6 years following IFN-α therapy was 88.3% (95% CI, 81.4–95.8%). The cumulative incidences of total chronic graft-versus-host disease (cGVHD) and severe cGVHD at 6 years following IFN-α therapy were 66.2% (95% CI, 55.5–77.0%) and 10.4% (95% CI, 3.6–17.2%), respectively. Multivariable analysis showed that an alternative donor was associated with a lower risk of relapse and the better disease-free survival. Thus, preemptive IFN-α therapy could clear MRD persistently, prevent relapse truly, and improve long-term survival in AML patients following allo-HSCT.